Reingeniería del sistema informático para el registro y control de Proyectos de Vinculación en la Facultad de Ciencias Administrativas Gestión Empresarial e Informática de la Universidad Estatal de Bolívar, año 2019 - Calderón Aguirre, Daniela Karolina (2019)
Nowadays, the Research and Linking Department of the Bolívar State University, performs the monitoring and control of linking projects, manually, helps with Excel tables, which serve as databases to manage the information of the executed projects , students with hours of bonding and teachers who have participated in them, that is why the development of a computer system that allows the registration and control of linking projects is proposed, which is part of the existing system, which It was not implemented for not complying with the technical specifications of the Tics department. With the implementation of the Information System, it is intended to streamline the processes of registration, supervision and control of linking projects, the generation of reports instantly, which is required to comply with the evaluation indicators of CACES. Keywords: System of Registration and Control of Linking Projects, Linking, Projects, Control.